Aplikasi Monitoring Siaran Televisi Lokal pada Komisi Penyiaran Indonesia Daerah (KPID) Sumatera Selatan - Imam Solikin; Nanda Firmansyah; Mulania Mulania (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2025)
The Regional Indonesian Broadcasting Commission (KPID) of South Sumatra is responsible for supervising and ensuring that local television broadcasts comply with applicable broadcasting regulations. However, the monitoring process, which is still conducted manually, results in limitations in effectiveness and efficiency. Therefore, this study aims to design and develop a local television broadcast monitoring application to help KPID South Sumatra carry out its supervision more optimally. The application is built using web-based technology that enables real-time monitoring and more systematic violation recording. The development method used is the Software Development Life Cycle (SDLC) Waterfall model, which includes the stages of analysis, design, implementation, testing, and maintenance. The results of this study indicate that the developed application can improve accuracy and efficiency in the local television broadcast monitoring process, as well as facilitate violation reporting. With this system, KPID South Sumatra can perform its supervisory duties more effectively and transparently.